Hubungan Tingkat Risiko Postur Kerja dan Faktor Individu dengan Keluhan Musculoskeletal Disorders Pekerja Mebel Tunjungsekar - Azizah, Aquila Ghafril; Yusuf, Mochamad; Sulistyorini, Anita; Kurniawan, Agung (National Journal of Occupational Health and Safety, 2024)
The high poverty rate in Indonesia can be addressed through the contribution of Micro, Small, and Medium Enterprises (MSMEs), which absorb approximately 57.78% of the workforce in the informal sector. However, this sector faces risks of workplace accidents and occupational diseases that can impact workers' productivity and well-being. Musculoskeletal Disorders (MSDs) account for 42% to 58% of all recorded occupational diseases globally. Preliminary observations identified symptoms of MSDs, such as neck stiffness and back pain, among furniture workers in the informal sector of Tunjungsekar. This study aims to determine the relationship between the risk levels of work posture and individual factors, including age, years of service, body mass index, education level, and physical activity, with MSD complaints among furniture workers. The methodology employed a cross-sectional design with a quantitative approach, involving 34 samples collected through total sampling techniques. The results indicated significant relationships between years of service (p=0.028) and education level (p=0.043) with MSD complaints, while the variables of work posture risk (p=0.437), age (p=0.644), body mass index (p=0.638), and physical activity (p=0.528) did not show significant associations. In conclusion, workers with over 10 years of service and low education levels are at a higher risk of experiencing MSD complaints. Keywords: musculoskeletal disorders, furniture workers, informal sector.